EVALUATION OF THE USE OF ANTIHYPERTENSIVE MEDICINES INPATIENT PREECLAMPSIA PATIENTS IN DATU SANGGUL RANTAU HOSPITAL - M. Ferdy Yahya Ramadhan; Tuty Mulyani; Herda Ariyani (LPPM - Universitas Muhammadiyah Banjarmasin, 2022)
Preeclampsia is a disorder in pregnant women characterized by hypertension and proteinuria after 20 weeks of gestation. The purpose of this study was to determine the description and use of antihypertensive drugs in inpatients of Preeclampsia patients at RSUD Datu Sanggul Rantau for the period January-December 2020. This research is descriptive non-experimental. Research data collection was carried out retrospectively by looking at medical records. The sampling method used purposive sampling method by considering the inclusion and exclusion criteria. The research sample included in the inclusion criteria was 60 medical records (patients). The data obtained were then compared with the 2016 POGI Preeclampsia reference standard and the NICE guidelines. The results of this study showed that the antihypertensive drugs used were nifedipine in 42 patients (70%) and a combination of nifedipine and methyldopa in 18 patients (30%). Evaluation of drug use obtained results to adjust the drug to 60 patients (100%), adjust the dose to 60 patients (100%), adjust the frequency to 59 patients (98.33%), adjust the duration of administration to 60 patients (100%). The average blood pressure when first admitted to the hospital was 166.5/106.7 mmHg. And the average blood pressure when leaving the hospital was 130.96/85.66 mmHg. As well as the success of reducing blood pressure as many as 60 patients (100%) managed to achieve the desired target.